Cost and impact analysis of sea level rise on coastal Vietnam - Paul S. Chinowsky; Amy E. Schweikert; Niko L. Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The Development under Climate Change research effort provides a basis for determining quantitative impacts on infrastructure from climate change. This paper provides results of an analysis of sea level rise impacts on road infrastructure in Vietnam. The study utilizes a quantitative approach for determining these impacts through engineering-based models that estimate the impact of sea level rises on road infrastructure. Through this approach, the cost impact of sea level rises on the coastal regions of Vietnam are presented.
Keywords: Q54; O44; O55; 330; Infrastructure; climate; vulnerability; resilience; adaptation